Environmental and Climate Challenges: Implications for Food Safety, Food Security, and Public Health Protection - Panunzio, Michele Fernando; Montagna, Maria Teresa; Russo, Rachele Maria (Annali di Igiene Medicina Preventiva e di Comunità, 2025)
Climate change poses a significant threat to global Food safety and security, but it also offers a unique opportunity to transform food systems towards more sustainable and resilient practices.